The Naturalist Society - Vaughn, Carrie (47 North, 2024)
In this magical tale of self-discovery from New York Times bestselling author Carrie Vaughn, a young widow taps into the power that will change the world -- if the man's world she lives in doesn't destroy her and her newfound friends first.